PLANT HEALTH MONITORING TECHNOLOGY WITH ARTIFICIAL INTELLIGENCE IN FRANCE - Faisal Razak; Rina Farah; Haziq Idris; Ardi Azhar Nampira (Techno Agriculturae Studium of Research, 2025)
This study explores the role of artificial intelligence (AI)-based plant health monitoring technology in France, which is expected to improve the efficiency of early detection of plant diseases and optimize the use of agricultural resources. The background of this research is based on the urgent need to increase agricultural productivity and reduce negative impacts on the environment. The purpose of this study is to test the effectiveness of AI in detecting plant health problems and provide data-driven recommendations for farmers. This study uses a mixed approach, with quantitative data from farmer surveys and qualitative data from interviews and case studies in major agricultural regions in France. The results showed that 80% of farmers reported an increase in early detection of diseases, and 75% reported a reduction in pesticide use. In conclusion, AI is playing an important role in supporting sustainable agriculture in France, although challenges in access to technology still need to be addressed. Further research is needed to explore ways to expand the adoption of this technology among smallholders.